Setting, Age, and Intensity Influence Responses to Exercise in Young Endurance Runners. Issue 3 (June 2020) - Reich, Alexander H.; Queathem, Elizabeth J.
We investigated the effects of exercise setting (indoor treadmill vs. outdoor trail), age (17 middle school, 18 high school, and 13 college participants), and level of exertion (Borg Ratings of Perceived Exertion of 10, 12, and 16 on a 22-point scale) on young male endurance runners' heart rate (HR), running speed, attentive focus, and affect. Three-way analyses of variance revealed that on the outdoor trail (vs. indoor treadmill), HR and speed were higher ( p < .001) and attentive focus was more dissociative ( p = .047). There were significant Age × Setting interactions for HR ( p = .047), speed ( p = .023), and attentive focus ( p = .002), with older participants exhibiting a greater increase in speed and HR and a greater shift toward dissociative focus on the outdoor trail. Three-way analyses of variance also yielded significant Age × Time interactions on components of the Physical Activity Affect Scale in that younger participants exhibited larger declines in positive affect ( p = .003) and tranquility ( p < .001) and larger increases in fatigue ( p < .001) as a result of the running session. Our data suggest that either runners develop more positive responses to exercise as they mature or those young runners who experience running more negatively tend to drop out of running so that the remaining older participants continuing to run are those who experience exercise positively.